2021
DOI: 10.1002/jmri.27692
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Radiomics‐Based Machine Learning Prediction of Clinically Significant Prostate Cancer in Equivocal PI‐RADS 3 Lesions

Abstract: Background While Prostate Imaging Reporting and Data System (PI‐RADS) 4 and 5 lesions typically warrant prostate biopsy and PI‐RADS 1 and 2 lesions may be safely observed, PI‐RADS 3 lesions are equivocal. Purpose To construct and cross‐validate a machine learning model based on radiomics features from T2‐weighted imaging (T2WI) of PI‐RADS 3 lesions to identify clinically significant prostate cancer (csPCa), that is, pathological Grade Group ≥ 2. Study type Single‐center retrospective study. Population A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
1
27
0
2
Order By: Relevance
“…Hectors et al. ( 19 ) recently constructed a random forest classifier based on T2WI radiomics features to predict CsPCa within PI-RADS 3 lesion, and the AUC was 0.76 in the test set. Giambelluca et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hectors et al. ( 19 ) recently constructed a random forest classifier based on T2WI radiomics features to predict CsPCa within PI-RADS 3 lesion, and the AUC was 0.76 in the test set. Giambelluca et al.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, texture analysis could further stratify PI-RADS 3 lesions into indolent or clinically significant PCa (csPCa) nodules, thus avoiding unnecessary biopsies [ 12 , 19 , 21 ]. The paper published by Hectors et al [ 12 ] showed a sensitivity and specificity of 75% and 79.6%, respectively, with an AUC of 0.76 regarding the detection of csPCa among PI-RADS 3 lesions ( p = 0.022), while mpMRI alone registered a sensitivity of 38.24% and a specificity of 53.85% for PI-RADS 3 tumors [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, a frequently admitted limitation is the lack of differentiation between peripheral and transitional zone nodules. While some studies purposefully limit the investigation protocol to the peripheric lesions, being considered more obvious and well-defined, thus suitable for designing a PCa detection prototype [ 10 , 14 , 16 ], others were restricted by the sample population size, which did not allow a separate analysis of peripheral and transitional lesions [ 12 , 24 , 25 , 26 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on intelligent diagnosis of PI-RADS 3 lesions were limited to simple imaging features (17)(18)(19), without considering the additional diagnostic value of clinical indicators. Compared with these similar studies, this study fused clinical indicators and imaging features when designing the model and proved that the two are complementary in the differentiation of benign and malignant prostate lesions.…”
Section: Clinical-radiomic Modelmentioning
confidence: 99%